Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1016/j.cjco.2020.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Facilitators to Using Statins: A Qualitative Study With Patients and Family Physicians

Abstract: Background Despite their proven efficacy to reduce cardiovascular disease, statin medication use remains low in individuals at high risk of cardiovascular disease considering their widespread availability and safety. Our objective was to explore the perspectives of patients and family physicians with regard to the barriers and facilitators of statin use in primary care. Methods In this qualitative descriptive study, we conducted 2 focus groups with patients (number, n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 41 publications
1
19
0
2
Order By: Relevance
“…Primary care providers may also face additional barriers such as large workloads, imbalance between expertise and increasing job demands, and lack of team support [ 17 19 ]. At the patient level, barriers to statin uptake in the general population include medication burden, concerns about side effects, and uncertainty about benefits [ 20 23 ]. For the care of PLWH specifically, barriers to statin uptake could include those that interfere with antiretroviral therapy and implementation of primary care guidelines more generally, such as lack of perceived need for treatment, lack of engagement in medical care, and psychosocial factors and life circumstances such as mental health issues, drug and alcohol use, stigma, and unstable housing [ 14 , 24 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Primary care providers may also face additional barriers such as large workloads, imbalance between expertise and increasing job demands, and lack of team support [ 17 19 ]. At the patient level, barriers to statin uptake in the general population include medication burden, concerns about side effects, and uncertainty about benefits [ 20 23 ]. For the care of PLWH specifically, barriers to statin uptake could include those that interfere with antiretroviral therapy and implementation of primary care guidelines more generally, such as lack of perceived need for treatment, lack of engagement in medical care, and psychosocial factors and life circumstances such as mental health issues, drug and alcohol use, stigma, and unstable housing [ 14 , 24 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further information about patient education, shared decision-making and clinical decision support tools are described in our other report from this work. 16 Open access…”
Section: Patient Results and Informationmentioning
confidence: 99%
“… 16 On the other hand, patients often experience or fear side effects, or are simply averse to taking additional medications. 16 Furthermore, patients that face social disadvantages such as low income, lack of health insurance, and minority race are more likely to not use statins. 17 A large US-based survey found that side effects were common and that many former statin users were unsatisfied with the explanation provided by their prescriber about the importance of the medication.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, nowadays, many people prefer to use nutraceuticals due to interest in 'natural' avenues of disease control, and the concern of potential drug interactions, long-term safety, and the economic implications of long-term (or life-long) dependence on drugs [5,6]. Moreover, some of the medications used to treat hyperlipidemia e.g., statins have side effects such as nausea, headaches, myalgias, memory loss and cognitive function impairment, and increased risk of diabetes [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%